A autonomia financeira da mulher como mecanismo para romper com o ciclo da violência doméstica e familiar a partir do microempreendedorismo individual - OLIVEIRA, Beatriz Alencar Sobreira de (2024)
It is necessary to understand that the scenario of domestic and family violence against women is a reality faced by many families in Brazil. Then, from the analysis of works and data on the topic, the aspect of financial dependence emerges as one of the factors for the perpetuation of the cycle of violence. The woman's lack of ability to support herself and the need to provide for her family's subsistence are circumstances that contribute to the maintenance of situations of violence experienced. The vulnerable condition of this woman is undoubted, the central idea of this study, and it is crucial to propose ways to put an end to this scenario. Because of this, it is essential to think about how to propose alternatives that aim to help women who are victims of violence have opportunities to generate income, in order to leave an abusive relationship. Therefore, this article aims to analyze women's financial autonomy, achieved through individual micro-entrepreneurship, as one of the mechanisms for breaking the cycle of domestic and family violence. This is because the importance of female entrepreneurship can be seen, which can be understood as a way for women to earn income and promote their livelihood and that of their children. Entrepreneurship appears as a possibility for women who are victims of domestic violence to find ways to break the cycle. This research will focus on individual micro-entrepreneurship as a form of carrying out business activity, with fewer requirements being requested for the businesswoman's regularization, an aspect that facilitates and encourages the promotion of the entrepreneurial profile.